Penerapan Metode Daring Sebagai Optimalisasi Media Pembelajaran Bahasa Inggris Masyarakat Milenial Di Masa Pandemi Covid-19 - Hilda - Hastuti; Puspita - Dewi; Riyana Rizki Yuliatin; Abdul - Muhid; Erwin - Suhendra; Wiya - Suktiningsih (Edumedia Solution, 2022)
The level of awareness about education in general and the ability to speak English is still low, especially in the millennial community, so it is necessary to make innovations in learning English. In order to support the implementation of English language learning in millennial communities during the COVID-19, it is necessary to apply an online method. During the pandemic, the government's efforts, one of which is face-to-face learning, cannot be done because it is to reduce and prevent the spread of COVID-19. Based on this explanation, our team held a devotion activity by the title